PEMBINAAN IMAN DALAM PELAYANAN MISDINAR DI PAROKI SANTO CORNELIUS MADIUN - Robertus Joko Sulistiyo; Pascalis Secundus Setwin Budiarto (Bahasa Indonesia, 2018)
Acolyte is the altar servers during the Eucharist celebration. This service is a noble service because serving God. However, these services are often not experienced as a noble and meaningful services that often made acolyte to comit a lot of mistakes and did not focus on these services. This study used qualitative research methods designed to answer the research question: to what extent acolyte has understood the meaning, significance of acolyte services, acolyte faith formation and acolyte faith formation programs in the parish of Saint Cornelius Madiun; how deep the impact of acolyte faith formation programs on the development of acolyte is faith, and what are the acolyte expectations for faith formation programs? Qualitative research results revealed that all respondents were able to explain well the questions posed by the researcher. But at the acolyte faith formation program, nine (90%) of respondents was only able to mention the faith formation programs without deeply explaining. Then the acolyte faith formation program that needs to be done are including recollection because this activity have long not running.